Extreme Teaming: Lessons in Complex, Cross-Sector Leadership - Edmondson, Amy C.; Harvey, Jean-Francois (Emerald Publishing, 2017)
Extreme Teaming Lessons in Complex, Cross-Sector Leadership Today’s global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today’s global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries – that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.

Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

Strategies for learning from failure - Edmondson, Amy C. (Harvard Business Review, 2011)